Development of Supply Curves for Biodiversity Offsets on Agricultural Land - a Case Study from the Stuttgart Region - Christian Sponagel; Hans Back; Elisabeth Angenendt; Enno Bahrs (German Journal of Agricultural Economics (GJAE), 2021)
Impacts on nature and landscape are to be offset in accordance with different nature conservation acts in various European countries. In Germany in particular, biodiversity offsets can also be made in advance, for instance, by booking them into eco-accounts, and then allocating them to an intervention. In Baden-Wur̈ttemberg, these offset measures are assessed in eco credits in accordance with the Eco Account Regulation (OK̈VO). As a means of income diversification, farmers can voluntarily implement offset measures on their land, and then generate and sell corresponding eco credits. Using a geodata-based model, the potential for implementing biodiversity offsets on arable land - areas with major eco credit potential - is analysed from an economic perspective. The Stuttgart Region is a steadily growing conurbation in south-west Germany. It serves as a study region since the loss of farmland due to large-scale construction measures and the related offsetting are a major issue here. In the analysis, the gross margins of the crops grown, their yield capacity, the associated standard land values and the costs of possible offset measures are used to determine the net present value of the arable land at parcel level. From a theoretical point of view and depending on the market price for eco credits, there is a significant potential for offset measures on arable land. Production-integrated compensation (PIC) - an extensification of arable land use - is less economically viable than the conversion of arable land into grassland or its utilisation for nature conservation. There are major spatial disparities between the city of Stuttgart and the surrounding districts. The implementation of biodiversity offsets is not economically viable at a price of less than exteuro 1.00 per eco credit in the city of Stuttgart. By contrast, in surrounding districts, offset measures may be economically viable and implemented on a large scale for less than exteuro 0.30. This is particularly relevant as the districts concerned are located in the same natural area as the city of Stuttgart and the eco credits can, therefore, be attributed in the event of interventions. Based on derived supply curves, decision-makers can see the scale of additional costs of biodiversity offset measures if they are implemented in a spatially restricted region. The analyses presented here can help decision-makers to more easily weigh up the desired natural characteristics and economic effects in the context of agricultural land.
Keywords: 330; production-integrated compensation; eco credits; ag-ricultural income; nature conservation; biodiversity offsets; a gri-environmental policy